Vertebrobasilar Artery Encasement by Skull Base Chordomas: Surgical Outcome and Management Strategies. Issue 4 (23rd April 2020) - Champagne, Pierre-Olivier; Passeri, Thibault; Jabre, Roland; Bernat, Anne-Laure; Voormolen, Eduard H; Froelich, Sébastien
Abstract: BACKGROUND: Vascular encasement by skull base chordomas can increase surgical risk and hinder completeness of resection. However, the evidence behind this remains anecdotic. OBJECTIVE: To give a better portrayal of chordomas encasing vertebrobasilar arteries mainly in regard of surgical vascular risk and its impact on extent of resection. METHODS: A retrospective cohort study comparing skull base chordomas with encasement (≥180 o encirclement) of the vertebrobasilar arteries to a control group of skull base chordomas with intradural extension. Data gathered involved pre- and postoperative volumetric analysis of the tumor, degree of encasement of involved vessel, occurrence of complication, and survival data including progression-free survival (PFS) and overall survival (OS). RESULTS: A total of 24 patients with vertebrobasilar encasement were included in the study and an equal number of control cases were randomly selected from the same time period, totalizing 48 patients. Lower clival tumors with condyle involvement were more likely to have encasement. Gross total resection (GTR) rate was significantly lower in the encasement group (13% vs 42%, P  = .023). Rates of postoperative new neurological deficit, CFS leak and 30 d postoperative mortality were not statistically different between groups. There was no statistically significant difference in mean PFS ( P  = .608) and OS ( P  = .958). CONCLUSION: Skull base chordomas encasing vertebrobasilar arteries are highly challenging tumors. This study demonstrates that although safe resection is possible, GTR is hindered by the presence of encasement. We advocate letting the tumor's adherence to vessels lead the resection, leaving a small piece of tumor behind if adherent to the vessels.